2000
DOI: 10.1046/j.1468-3083.2000.00014.x
|View full text |Cite
|
Sign up to set email alerts
|

One‐year treatment of chronic urticaria with mizolastine: efficacy and safety

Abstract: Mizolastine improves CU symptoms, and these improvements are sustained over 12 months with no loss of drug sensitivity. No specific side-effects are associated with its long-term use in the current study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Several clinical studies demonstrated the efficacy of mizolastine in treating the symptoms of CIU [60,61,62,63]. In a 4-week multi-centre, double-blind, parallel-group study of 247 patients with CIU, mizolastine 10 mg/day was shown to be as effective as loratadine 10 mg/day with respect to reduction of pruritus and episodes of urticaria, compared with placebo (p < 0.009) [61].…”
Section: Chronic Idiopathic Urticariamentioning
confidence: 99%
See 3 more Smart Citations
“…Several clinical studies demonstrated the efficacy of mizolastine in treating the symptoms of CIU [60,61,62,63]. In a 4-week multi-centre, double-blind, parallel-group study of 247 patients with CIU, mizolastine 10 mg/day was shown to be as effective as loratadine 10 mg/day with respect to reduction of pruritus and episodes of urticaria, compared with placebo (p < 0.009) [61].…”
Section: Chronic Idiopathic Urticariamentioning
confidence: 99%
“…Lorette et al [63] reported the long-term efficacy and safety of daily oral mizolastine (10 or 15 mg) in a 1-year open-label trial of 127 patients with CIU. After 2 months of therapy, patients receiving mizolastine experienced improvements in overall discomfort, itching, angioedema and a reduction in the number and size of wheals.…”
Section: Chronic Idiopathic Urticariamentioning
confidence: 99%
See 2 more Smart Citations
“…A study aiming to assess the long-term safety of mizolastine has shown that one-year mizolastine treatment did not change the QT c intervals, and no significant changes in mean systolic and diastolic blood pressures have occurred [65]. However, concentrations of mizolastine higher than those achieved during standard therapy are able to block HERGrelated potassium channels [66].…”
Section: Mizolastinementioning
confidence: 99%